Dinamika Konsumen Islami : Mempertimbangkan Peran Celebrity Endorser, Social Media Marketing dan Product Variation Terhadap Minat Beli Local Brand Ventela Pada Mahasiswa FEB Universitas Islam Nahdlatul Ulama Jepara - Zulfa, Kurnia; Arifin, Samsul (Jurnal Ilmiah Ekonomi Islam, 2024)
The study aims to identify patterns of Islamic consumer response to the role of celebrity endorsers, social media marketing, and product variations that influence ventela buying interest at the Faculties of Economics and Business, Islamic University Nahdlatul Ulama Jepara. This research is quantitative. The data analysis method used in this study is linear regression analysis with the help of SPSS 22. The tests used in the study are instrumental test, classical assumption test and hypothesis test. In this study, there are 94 samples. The data used are primary data obtained through the spread of questionnaires. The results show that partly celebrity endorsers have a positive but not significant influence on purchase interest, social media marketing has a positive and significant impact on purchase interest, and product variation has a significant and positive impact on purchase interest. Simultaneously, celebrity endorser variables, social media marketing and product variation have a positive and significant influence on purchasing interest.